Pancasila sebagai Paradigma Politik Pembaruan Hukum Pidana Nasional - Rossa Ilma Silfiah; Heppy Hyma Puspytasari (Fakultas Hukum Universitas Islam Indonesia, 2024)
Criminal law politics, also known as national criminal law reform policy, is an integral part of social policy in general. This is because the existence of criminal law is heavily influenced by social changes in society. The state must monitor social changes to ensure that they remain within the boundaries of Pancasila ideology. Pancasila is a forum for living together for Indonesia's diverse nation so that it remains closely bound as a united nation, Bhinneka Tunggal Ika. Pancasila appears in the Preamble to the 1945 Constitution, which declares Indonesia's independence. As a result, the current Criminal Code in Indonesia must be updated to reflect the reform era. Several articles have also undergone changes, with the government making additional provisions regarding specific articles. As a result, comprehensive reform is required to ensure that criminal law can achieve its goals, which are to protect society and promote social welfare. Using normative methods, this study investigates Pancasila as a paradigm for determining the direction of criminal law policies. It also employs a policy-oriented and a value-oriented strategy. Because Pancasila is a national and state ideology.